External experience for the execution of exchange regulation and possibilities of its application in Ukraine - Barash, Ye.; Kryvytskyi, Yu.; Ablamskyi, S. Ye.; Абламський, С. Є.; Абламський Сергій Євгенович (Baltic Journal of Economic Studies. - 2018. - Vol. 4, №. 1. - P. 25-30, 2018)
Проведено порівняльно-правове дослідження нормативно-правових актів, що визначають правові засади запровадження валютного регулювання в окремих зарубіжних країнах та в Україні. Запропоновано шляхи вдосконалення вітчизняного законодавства у цій сфері. Досліджено досвід валютного регулювання в деяких європейських країнах, США, Китаї та Україні.

The aim of the article is to conduct a comparative legal study of statutory legal acts, which defne the legal framework for the implementation of currency regulation in some foreign countries and in Ukraine and which determine on this basis ways to improve domestic legislation in this area. The subject of the research is the experience of currency regulation in some European countries, USA, China, and Ukraine. Methodology. The research is based on a comparison of foreign exchange regulation in Ukraine and in foreign countries. Advantages and disadvantages of diﬀerent modes of state control over currency circulation are determined, on the basis of the analysis of peculiarities of the state regulation of currency circulation in the United Kingdom, Germany, France, Poland, the USA, China, and in some other countries: from ﬂoating rate regime to rigorous state control. On the basis of the comparative legal study of certain provisions of the administrative legislation of Ukraine, the possibilities and limits of the application of positive foreign experience in this feld are determined. The results of the study have shown that in order to implement foreign exchange management experience, it is necessary to postpone the fnal transition untill establishing a ﬂoating rate regime. It is possible to make it by reinforcing state interference. At the same time, it is necessary to strengthen currency control not only over the implementation of foreign exchange operations but also over the activities of subjects that determine the state policy in the feld of currency regulation, as well as over those, who directly carry out the corresponding activity using the tools specifed by provisions of the current legislation. Practical impact. The positive experience of the formation of the foreign exchange market in foreign countries shows that the gradual transition from a fxed to a ﬂoating exchange rate is the beginning of a natural market exchange rate and the equalization of the balance of payments and the gradual release of the national economy from the pressure of administrative and corruption restrictions. Value/originality. Conducting the comparative analysis of foreign exchange regulation in foreign countries is the basis for developing the most promising directions for the development of domestic legislation in this feld.

Проведено сравнительно-правовое исследование нормативно-правовых актов, определяющих правовые основы введения валютного регулирования в отдельных зарубежных странах и в Украине. Предложены пути совершенствования отечественного законодательства в этой сфере. Исследован опыт валютного регулирования в некоторых европейских странах, США, Китае и Украине.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u zarubizhnomu vydanni; publikatsii u WoS; Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; foreign experience; зарубіжний досвід; зарубежный опыт; currency regulation; валютне регулювання; валютное регулирование; exchange rate; курс обмена; курс обміну; currency control; валютный контроль; валютний контроль; countries of EU; страны Европейского союза; країни Європейського Союзу